2019
DOI: 10.1108/bfj-10-2018-0692
|View full text |Cite
|
Sign up to set email alerts
|

The impact of consumption value on consumer behaviour

Abstract: Purpose The purpose of this paper is to investigate the influence of halal concern as well as emotional and epistemic values on consumer behaviour in the choice and purchase of halal-certified food supplies. Design/methodology/approach This study used a quantitative methodology of convenience sampling to collect survey data from 1,550 Muslim respondents in Malaysia. It also employed multiple regressions by covariance-based structural equation modelling in the data analysis as well as in the validation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 57 publications
2
51
2
7
Order By: Relevance
“…Some studies using TCV have emphasized the potential relations among the values. For instance, the emotional value was claimed to be an accompanying element derived from the consumption value of goods (Muhamed et al, 2019). Emotional value as a moderator was found to alter the relationships between the other values of the TCV and green choice behaviour; encouraging this value was suggested for improving the effects of the other values on green product choice (Khan & Mohsin, 2017).…”
Section: Conflicting Issues For Independency Of Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies using TCV have emphasized the potential relations among the values. For instance, the emotional value was claimed to be an accompanying element derived from the consumption value of goods (Muhamed et al, 2019). Emotional value as a moderator was found to alter the relationships between the other values of the TCV and green choice behaviour; encouraging this value was suggested for improving the effects of the other values on green product choice (Khan & Mohsin, 2017).…”
Section: Conflicting Issues For Independency Of Valuesmentioning
confidence: 99%
“…Regarding goods, the TCV has been used to explain product choice behaviour with consumption value. The epistemic and emotional values were found to have significant positive effects on decision making about foods with a halal certificate (Muhamed et al, 2019), whereas social and emotional values were reported to encourage consumer experiences with halal cosmetics (Mohamed & Li, 2017).…”
Section: Product Contextmentioning
confidence: 99%
“…1) Halal Supply Chain Management -Strategic Orientation -Firm Performance (FP) Theodosiou et al (2012) point out that it is important to investigate the role of intervening variable that mediates the relationship between strategic orientation and performance outcome. The literature emphasizes the necessary to inquire into the relationship between one essence of strategic orientation with other complimentary orientation such as innovation, organizational learning, quality, productivity, and entrepreneurship (Hurley & Hult, 1998;Marinova et al, 2008;Menguc, 2006;Muhamed et al, 2019;Theodosiou et al, 2012;Zhou et al, 2005). Such relationship develops the following proposition and illustrated in Figure 4: (2) 𝐻𝑆𝐶𝑀 = 𝑖 + 𝛼𝑆𝑂 + 𝑒2…”
Section: Model and Prepositionmentioning
confidence: 99%
“…Penelitian tentang produk halal sudah banyak dilakukan dalam beberapa tahun terakhir. Sebagian besar terkait dengan produk makanan dan minuman halal (Ahmadova & Aliyev, 2020;Akın & Okumuş, 2020;Ali, Sherwani, Ali, Ali, & Sherwani, 2020;Amalia et al, 2020;Bashir, 2019;Hanafiah & Hamdan, 2020;Iranmanesh, Mirzaei, Parvin Hosseini, & Zailani, 2019;Khan, Akhtar, Ansari, & Dhamija, 2020;Muflih & Juliana, 2020;Muhamed, Ab Rahman, Mohd Hamzah, Che Mohd Zain, & Zailani, 2019;Wibowo, Permana, Hanafiah, Ahmad, & Ting, 2020) Penelitian tentang produk kosmetik halal (Haque, Anwar, Tarofder, Ahmad, & Sharif, 2018;Karoui & Khemakhem, 2019;Khan, Sarwar, & Tan, 2020;Suhartanto et al, 2020;Suparno, 2020). Akan tetapi belum ada yang mengkaji lebih spesifik tentang produk kosmetik halal, penelitian ini mencoba melihat secara spesifik tentang produk kosmetik asal Korea Selatan.…”
Section: Pendahuluanunclassified